2022
DOI: 10.17507/jltr.1301.17
|View full text |Cite
|
Sign up to set email alerts
|

Saudi EFL Learners’ FLA: Levels, Causes, Gender, and Impact on Academic Performance

Abstract: As a common psycholinguistic barrier that hinders EFL learning, Foreign Language Anxiety (FLA) has become an important study area in EFL learning and teaching. This study investigated the level and causes of FLA among 69 first-year EFL learners at Bisha University in Saudi Arabia. The influence of gender on the level of FLA was also examined. Moreover, the study examined the impact of FLA on the participants' language achievement. The researchers utilized a modified version of the Foreign Language Classroom An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In this sense, practicing in public, including attempts and failures, could result in embarrassment, disappointment and apprehensive actions. This is in line with previous research findings (Alsalooli and Al-Tale, 2022; Mahdi, 2015) which revealed a significant relationship between EFL learners' CA and CC. The tendency toward apprehension showed up in FL contexts due to unsatisfactory tasks, a lack of input flood and first language overuse.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this sense, practicing in public, including attempts and failures, could result in embarrassment, disappointment and apprehensive actions. This is in line with previous research findings (Alsalooli and Al-Tale, 2022; Mahdi, 2015) which revealed a significant relationship between EFL learners' CA and CC. The tendency toward apprehension showed up in FL contexts due to unsatisfactory tasks, a lack of input flood and first language overuse.…”
Section: Discussionsupporting
confidence: 93%
“…2.2 Communication apprehension (CA) and foreign language (FL) learning FL Apprehension has emerged as a substantial area of research in EFL teaching and learning (Alsalooli and Al-Tale, 2022). Previous research has revealed that apprehension is a domain in oral communication in EFL interaction.…”
Section: Heswbl 136mentioning
confidence: 99%
“…Students' encounter with "writing block" on tests is a good example of cognitive interference at the output stage (Cheng, 2004). According to Alsalooli and Al-Tale (2022), FLA "has become an important study area in EFL learning and teaching" (p. 145).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A growing number of studies have focused on gender differences and their correlation with written communication anxiety in the foreign language context (Alsalooli & Al-Tale, 2022;Al-Kubaisy, Hummadi, & Turki, 2019;Gerencheal, 2016;Liu, 2021;Mulyono, Liestyana, Warni, Suryoputro, & Ningsih, 2020) and reported inconsistent findings. For instance, Gerencheal (2016) investigated the differences in the anxiety level of third-year EFL learners at Mizan-Tepi University, Ethiopia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…English is the most spoken language in the world. The language used as lingua franca in global community (Alsalooli and Al-Tale', 2022). Therefore, become able to be fluent in English language is highly advantageous.…”
Section: Introductionmentioning
confidence: 99%